The Greek crisis and European modernity - Gropas, Ruby; Kouki, Hara; Triandafyllidou, Anna (Identities and Modernities in Europe, 2013)
This collection explores the current economic and political crisis in Greece and more widely in Europe. Greece is used to illustrate and exemplify the contradictions of the dominant paradigm of European modernity, the ruptures that are inherent to it, and the alternative modernity discourses that develop within Europe